2023
DOI: 10.1038/s41598-023-47448-3
|View full text |Cite
|
Sign up to set email alerts
|

Range area and the fast–slow continuum of life history traits predict pathogen richness in wild mammals

Jacqueline Choo,
Le T. P. Nghiem,
Ana Benítez-López
et al.

Abstract: Surveillance of pathogen richness in wildlife is needed to identify host species with a high risk of zoonotic disease spillover. While several predictors of pathogen richness in wildlife hosts have been proposed, their relative importance has not been formally examined. This hampers our ability to identify potential disease reservoirs, particularly in remote areas with limited surveillance efforts. Here we analyzed 14 proposed predictors of pathogen richness using ensemble modeling and a dataset of 1040 host s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The eco-evolutionary peculiarities of each viral group drive patterns of compatibility between mammals and viruses, as we partially captured by separately assessing different eco-evolutionary groups of viruses. By including multiple sides of viral diversity, we were able to pick up on trends that went undetected in previous studies where pathogen richness was analysed as a whole [ 4 , 65 ]. We found that larger mammals are carriers for several viral groups, but both fast- and slow-living species are exploited by multiple viral groups with different ecological, evolutionary and structural features.…”
Section: Discussionmentioning
confidence: 99%
“…The eco-evolutionary peculiarities of each viral group drive patterns of compatibility between mammals and viruses, as we partially captured by separately assessing different eco-evolutionary groups of viruses. By including multiple sides of viral diversity, we were able to pick up on trends that went undetected in previous studies where pathogen richness was analysed as a whole [ 4 , 65 ]. We found that larger mammals are carriers for several viral groups, but both fast- and slow-living species are exploited by multiple viral groups with different ecological, evolutionary and structural features.…”
Section: Discussionmentioning
confidence: 99%
“…We ran a Wilcoxon test to assess whether our selection of pseudo-negatives was biased by species' range size, and found that the median range size of pseudo-negatives was signi cantly larger than the median range size of a random sample of mammals (p < 0.001) but also signi cantly smaller than the median range size of positive species (p < 0.001). While this comparison highlighted that neither positive species nor pseudo-negative species are a representative sample of the average mammal in terms of range size (Figure S1), largerthan-random range size of pseudo-negatives is actually desirable as it may counterbalance the exceptionally large range size of positive species, which is probably due to a combination of sampling bias and exposure to pathogens (Choo et al, 2023). Our pseudo-negative protocol identi ed 1,117 pseudo-negative species that met the criteria.…”
Section: De Nition Of Host Statusmentioning
confidence: 99%